THE DESCRIPTIVE ANALYSIS OF THE SERVICE QUALITY DIMENSION OF MOBILE BANKING (M-BANKING) ON THE SATISFACTION OF SHARIA BANKING CUSTOMERS - Charissa Kezia Rahmawati; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research presents an initial study of customer satisfaction as measured by five mobile banking (m-banking) quality services dimensions using descriptive statistics and mean score. The survey data were obtained from 100 respondents of mobile banking (m-baking) users by using a purposive sampling method. The data is processed using validity and reliability test to check the quality of the data. The results shown in this research are explanatory or extracting information on which factors the customer shows high and low satisfaction.Keywords: Customer Satisfaction, Descriptive Statistic, Mobile Banking, Quality Service DimensionREFFERENCE Arcand, M., Promtep, S., & Brun, I. (2016). Mobile banking service quality and customer relationships. International Journal of Bank Marketing, 35(7), 1068-1089. DOI: https://doi.org/10.1108/IJBM-10-2015-0150Azwar, S. (2012). Penyusunan skala psikologi, edisi kedua. Yogyakarta: Pustaka Pelajar.Baabdullah, A. M., Alalwan, A. A., Rana, N. P., Kizgin, H., & Patil, P. (2019). Consumer use of mobile banking (M-Banking) in Saudi Arabia: Towards an integrated model. International Journal of Information Management, 44(September 2018), 38–52. Clemes, M. D., Cohen, D. A., Wang, Y., Clemes, M. D., Cohen, D. A., & Wang, Y. (2013). Understanding Chinese university students ’ experiences: an empirical analysis. Asia Pacific Journal of Marketing and Logistics, 25(3), 391-427. DOI: 10.1108/APJML-07-2012-0068Hamidi, H., & Safareeyeh, M. (2019). A model to analyze the effect of mobile banking adoption on customer interaction and satisfaction: A case study of m-banking in Iran. Telematics and Informatics, 38(May 2019), 166–181. Harris, L. C., & Goode, M. M. H. (2010). Online servicescapes, trust, and purchase intentions. Journal of Services Marketing, 24(3), 230–243. Kotler, Phillip, Amstrong, & Gary. (2012). Principles of marketing (14th ed.). New Jersey: Pearson Hall.Lee, K. C., & Chung, N. (2009). Understanding factors affecting trust in and satisfaction with mobile banking in Korea: A modified DeLone and McLean’s model perspective. Interacting with Computers, 21(5–6), 385–392. Mehmet Haluk Koksal. (2016). The intentions of Lebanese consumers to adopt. International Journal of Bank Marketing, Vol. 34(3), 327-346. DOI: https://doi.org/10.1108/IJBM-03-2015-0025OJK. (2017). Prinsip dan konsep dasar perbankan syariah. Jakarta: OJK.Rustam, B. R. (2018, Oktober). Perbankan syariah era digital. Koran Jakarta.Shaikh, A. A., & Karjaluoto, H. (2015). Telematics and Informatics Mobile banking adoption: A literature review. Telematics and Informatics, 32(1), 129–142. Tam, C., & Oliveira, T. (2015). Literature review of mobile banking and individual performance. International Journal of Bank Marketing, 35(7), 1044-1067. DOI: https://doi.org/10.1108/IJBM-09-2015-0143Toor, A., Hunain, M., Hussain, T., Ali, S., & Shahid, A. (2016). The impact of E-banking on customer satisfaction: Evidence from banking sector of Pakistan. Journal of Business Administration Research, 5(2), 27–40. Yuliardi, R., & Nuraeni, Z. (2017). Statistika penelitian plus tutorial SPSS, edisi pertama. Yogyakarta: Innosain.